(untitled) - Peppers, Don (New York)
Today, technology allows us to sell more goods to fewer people, which is far more efficient than selling fewer goods to more people. Peppers, an advertising executive, and Rogers, a marketing scholar, set out their new marketing paradigm in detail. A one-to-one competitor focuses on "share of customer" rather than the mass-marketer's "share of market." Learn to collaborate with the customer to build loyalty and build your opportunities for future profit
Keywords: Consumers' preferences,Customer relations,Market segmentation,Sales promotion